IMPAСT OF ARTIFICIAL INTELLIGENCE ON THE FIELD OF LAW (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article examines the impact of artificial intelligence on the field of law. The article explores the significance of artificial intelligence in automating legal processes, providing legal advice, and processing documents. Furthermore, it discusses how AI can create opportunities for detecting and preventing crime, as well as predicting court decisions. However, the introduction of AI in the legal field also brings numerous ethical and legal challenges, particularly regarding transparency in decision-making, the reduction of human involvement, and issues such as data privacy, which are also discussed.